2018
DOI: 10.1002/nop2.207
|View full text |Cite
|
Sign up to set email alerts
|

Dysmenorrhoea among students aged 18–45 years attending University in Uganda: A cross‐sectional multicenter study of three Universities in Uganda

Abstract: Aim Dysmenorrhoea presents as pain associated with menstruation. It is often an issue discussed privately, yet it continues to affect girls and women with grave impact on their education, social activities and work. This study sought to assess the factors associated with dysmenorrhoea among female students aged 18–45 years in three selected universities in Kampala Capital city, Uganda. Design and Methods The study was a cross‐sectional study conducted among 351 female s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
4
11
0
1
Order By: Relevance
“…The findings regarding dysmenorrhea are interesting because while congestive dysmenorrhea was associated with PMDD, spasmodic dysmenorrhea was not. We assessed dysmenorrhea using a validated measure and thus improved on the methodology used in previous studies among university students (Al-Jefout et al, 2015;Nakame et al, 2018;Yacubovich et al, 2019). Moreover, these studies did not differentiate between spasmodic and congestive dysmenorrhea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings regarding dysmenorrhea are interesting because while congestive dysmenorrhea was associated with PMDD, spasmodic dysmenorrhea was not. We assessed dysmenorrhea using a validated measure and thus improved on the methodology used in previous studies among university students (Al-Jefout et al, 2015;Nakame et al, 2018;Yacubovich et al, 2019). Moreover, these studies did not differentiate between spasmodic and congestive dysmenorrhea.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of dysmenorrhea among university students is high. Research assessing the prevalence of these symptoms among university students in Uganda, Israel and Spain report prevalence rates ranging between 76% and 86% (Fernandez-Martinez et al, 2018;Nakame et al, 2018;Yacubovich et al, 2019).…”
Section: Dysmenorrheamentioning
confidence: 99%
“…The prevalence of dysmenorrhea varies from 50% to 90% globally. Nakame et al [4] reported a range of more than 50% to 85% in Europe and America for the same and 60% to 85% in Asia [4]. Approximately 75% of people experience PMS, as reported by Wilbur et al [5], which includes emotional and physical symptoms that occur between one and two weeks before menstruation [5].…”
Section: Introductionmentioning
confidence: 94%
“…Status gizi baik pada remaja dapat diperoleh dengan konsumsi gizi seimbang sesuai kebutuhan pada masa remaja (Fairuz, 2010). Faktor lain yang berhubungan dengan dismenorea menurut penelitian lain adalah riwayat dismenorea dari ibu dan saudara perempuan, pre menstruasi syndrome (PMS), usia menarche, stress, latihan fisik (Barcikowska, 2020), keteraturan siklus menstruasi, pendidikan ibu (Helwa, 2018) sedangkan beberapa hal yang mempengaruhi status gizi selain IMT yang berhubungan dengan kejadian dismenorea meliputi konsumsi harian makanan manis (Nakame, 2019), sarapan pagi (Helwa, 2018), minum kopi mingguan (Al Matouq,2019) merokok, alcohol (Ju, 2015).…”
Section: Pembahasanunclassified